BUILDING COMPETITIVENESS AND BUSINESS RESILIENCE IN THE ENVIRONMENT OF DIGITAL ECONOMY – A RESEARCH IN A CHAIN OF SERBIAN PHARMACIES - Babic-Banković, Spomenka (Annals of Nursing, 2024)
Background: Digital health care encompasses the use of information and communication technologies (ICT) in improving processes related to health, prevention, diagnosis, and treatment of the diseased. Aim: The goal of this research is to explore the transformation of conventional pharmaceutical profession into digital roles.. Materials and Methods: The research was conducted in 2022 within a chain of five pharmacies named "Hygia Pharmacy" in Arandjelovac, Serbia, with 23 employees. The primary focus was to assess the impact of digitization on the company’s performance, competitiveness, and business resilience. An internet-based survey was conducted among the employees (initial, 3 months later and 6 months later). Results: The business resilience plan in the company was confirmed by 91% of respondents. Most respondents stated that they attend professional webinars (81%) and Zoom meetings (57%) to improve their competitiveness. All respondents rated online sales as positively impacting consumers in terms of shopping convenience, and mentioned that internal shipping and receiving documents facilitate work in the pharmacy. Most respondents (78%) gather professional information from digital sources (e-Pharmacy) compared to the paper form of the journal Pharmacy Practice. The survey revealed a downward trend in traditional working techniques compared to digital techniques, which showed an upward trend throughout all three testing cycles. Conclusion: The research conducted within Serbian pharmacies indicates that the digital economy and ICT have caused significant transformations in terms of improving the competitiveness and business resilience of pharmacists.